Interview with Varvara Rao, poet and activist on the Naxalite movement in Andhra Pradesh. Interviewed in Hyderabad by Shahriar Kabir and Abhijeet Majumdar, 16/10/1997 - Kabir, Shahriar.
Interview with Varvara Rao, poet and activist on the Naxalite movement in Andhra Pradesh. Interviewed in Hyderabad by Shahriar Kabir and Abhijeet Majumdar, 16/10/1997.